Diksyunaryong Filipino-English. - Philippines. Commission on the Filipino Language (Pasig, Metro Manila Komisyon sa Wikang Filipino, 1992)
This collection of different ethnic languages aims to be the benchmark for future dictionaries for the development of the National Language. This dictionary is intended for those who are studying the Filipino and English Languages.
Keywords: Filipino language -- English. -- Dictionaries; English language -- Filipino. -- Dictionaries